The Influence of Styrene/butadiene Ratio on the Self-assembly Behavior of SBS Modified Asphalt. Issue 1 (February 2021) - Yu, Caihua; Hu, Kui; Chen, Yujing; Li, Qi; Zhang, Taoli; Chen, Guixiang
Abstract: This work using molecular dynamic simulation to explore the micro mechanism of Styrene-butadiene-styrene (SBS) with light components (aromatics and saturates). The results indicate that the adsorption area decrease with the increase of S/B ratio. And with the increase of temperature, the adsorption area first increased and then decreased. Rutting factor experiments show that the rutting factor gradually decreases with increasing temperature and decreases with increasing S/B ratio, which is consistent with the findings of molecular dynamics simulations.